Evaluation of neuropsychological characteristics and attention bias in juvenile offenders, juvenile victims, and juveniles who have not participated in the criminal justice system - Patiz, Büşra; Bayraktar, Seda (Frontiers in Psychology, 2023)
Introduction The increasing inclusion of children in the criminal justice system as “juvenile offenders” and “juvenile victims” has recently emerged as a severe and multifaceted problem. This study evaluates whether juvenile offenders differ from juveniles who have not participated in the criminal justice system and juvenile victims regarding executive function skills and attentional bias. Method The participant group comprised 85 children aged 12–18, and the study setting was Turkey, utilizing one control group and two treatment groups with open criminal case files in Antalya Courthouse. The first treatment group consisted of 30 juvenile offenders; the second consisted of 30 juvenile victims. The control group consisted of 25 juveniles who were not juvenile offenders or victims. In this context, children’s executive functions were measured with the short-form Barratt Impulsivity Scale, the Raven Standard Progressive Matrices Test, the TBAG-form Stroop test, the Wisconsin Card Sorting Test, and the Istanbul 5 Cube Planning Test. Attentional bias was measured using a dot-probe task. Illiteracy, intellectual or developmental disability, and being a non-native Turkish speaker were the exclusion criteria for all three groups. Results The study found that the scores of the juvenile offender group on the Barratt Impulsivity Scale were significantly higher than the children in the juvenile victim group and the children in the control group. For other tests measuring executive functions, the control group’s scores were significantly higher than juvenile offenders and juvenile victims. Regarding attentional bias, the children in the control group exhibited less attentional bias to negative stimuli than the juvenile offenders and victims. Discussion Researchers have generally addressed the reasons that push children to crime and become victims of crime through individual, familial, and environmental reasons. However, the number of studies investigating the neuropsychological characteristics of children dragged into crime is relatively limited in our country. In addition, there is no study comparing the executive functions and attentional bias of children who are dragged into crime, victimized children, and children without a history of being dragged into crime and victimization. In this context, this study can highlight important implications for the judicial system regarding juvenile delinquency interventions.